1968
DOI: 10.1007/bf02541259
|View full text |Cite
|
Sign up to set email alerts
|

Composition of several types of Safflower seed

Abstract: The residue remaining after commercial extraction of oil from safflower seed has a greater potential as a source of animal feed or human diet supplement than is presently being realized. Safflower seed hull, kernel, and meal were analyzed to provide more information regarding their nutritive possibilities. Commercial and experimental normal hull varieties and experimental thin hull and striped hull varieties were hand separated into hull and kernel fractions and both fractions analyzed for protein, fat, fiber,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A major factor for the growing demand of safflower oil in the form of cooking or salad oil is its high linoleic acid content {78%}, which has some therapeutic value in preventing ather~ sclerosis (6,7). The oflcake protein increases to 40-60% from 17-22% protein in the seed (8), and is a good-quality pr~ tein with respect to essential amino acids (4). The quality of safflower kernel protein is comparable with soybean meal proteirL Only lysine is critically limiting, and methionine and isoleucine are borderline It contains enough histidine to meet the needs of children.…”
mentioning
confidence: 99%
“…A major factor for the growing demand of safflower oil in the form of cooking or salad oil is its high linoleic acid content {78%}, which has some therapeutic value in preventing ather~ sclerosis (6,7). The oflcake protein increases to 40-60% from 17-22% protein in the seed (8), and is a good-quality pr~ tein with respect to essential amino acids (4). The quality of safflower kernel protein is comparable with soybean meal proteirL Only lysine is critically limiting, and methionine and isoleucine are borderline It contains enough histidine to meet the needs of children.…”
mentioning
confidence: 99%
“…seeds from primary or secondary capitula may differ. Guggolz et al, (1968) reported that normal clean hull type varieties had low kernel percentage than the striped and thin hull type varieties. The kernel percentage varied from 50 to 62% (38 to 50% hull content) in normal clean hull type varieties and from 74 to 76% (24 to 26% hull content) in striped or thin hull type varieties.…”
Section: Plate1 Variability For Seed Morphological Traits In Safflower Genotypesmentioning
confidence: 99%
“…With the pressing need for a source of protein with high biological value, some research is now being directed toward meal improvement. The composition of the oil-free meal has been investigated recently (Guggolz et al, 1968), and feeding tests on chicks have been performed (Halloran, 1961;Kohler et al 1966; Kuzmicky and Kohler, 1968a, b;Kratzer and Williams, 1951;Valadez et al, 1965). Completely decorticated safflower meal contains 65% protein.…”
Section: Interestmentioning
confidence: 99%